Anton Nilsson et l’écho d’une bombe. Malmö, 1908-1917 - Lars Berggren; Roger Johansson (Cahiers d’histoire.)
Anton Nilsson (1887–1989) is one of the most famous people in the Swedish labour movement and a prominent activist with the status of an icon. He was a member of the Young Socialist movement in the working-class city of Malmö, he placed a bomb on the ship Amalthea, which housed 73 English strike breakers, in connection with an extensive dock worker conflict in the Swedish ports. Anton Nilsson was sentenced to death in a subsequent trial, but after extensive protests, also abroad, the death sentence was converted to life imprisonment. Following the “potato revolution” and as the first Social Democratic / Liberal government was elected, he was granted an amnesty in 1917 and released from captivity. On Midsummer's Eve 1919, Anton Nilsson took an international flight certificate and went to the young Soviet state to become a pilot in the Red Army. He remained an agitator throughout his life and participated as a centenarian in the First of May demonstration in Stockholm, where he then lived and later was also buried.